Extratropical storm inundation testbed: Intermodel comparisons in Scituate, Massachusetts. Issue 10 (7th October 2013) - Chen, Changsheng; Beardsley, Robert C.; Luettich, Richard A; Westerink, Joannes J.; Wang, Harry; Perrie, Will; Xu, Qichun; Donahue, Aaron S.; Qi, Jianhua; Lin, Huichan; Zhao, Liuzhi; Kerr, Patrick C.; et al.
Abstract : [1] The Integrated Ocean Observing System Super‐regional Coastal Modeling Testbed had one objective to evaluate the capabilities of three unstructured‐grid fully current‐wave coupled ocean models (ADCIRC/SWAN, FVCOM/SWAVE, SELFE/WWM) to simulate extratropical storm‐induced inundation in the US northeast coastal region. Scituate Harbor (MA) was chosen as the extratropical storm testbed site, and model simulations were made for the 24–27 May 2005 and 17–20 April 2007 ("Patriot's Day Storm") nor'easters. For the same unstructured mesh, meteorological forcing, and initial/boundary conditions, intermodel comparisons were made for tidal elevation, surface waves, sea surface elevation, coastal inundation, currents, and volume transport. All three models showed similar accuracy in tidal simulation and consistency in dynamic responses to storm winds in experiments conducted without and with wave‐current interaction. The three models also showed that wave‐current interaction could (1) change the current direction from the along‐shelf direction to the onshore direction over the northern shelf, enlarging the onshore water transport and (2) intensify an anticyclonic eddy in the harbor entrance and a cyclonic eddy in the harbor interior, which could increase the water transport toward the northern peninsula and the southern end and thus enhance flooding in those areas. The testbed intermodel comparisons suggest that major differences in the performance of the three models were caused primarily by (1) the inclusion of wave‐current interaction, due to the different discrete algorithms used to solve the three wave models and compute water‐current interaction, (2) the criterions used for the wet‐dry point treatment of the flooding/drying process simulation, and (3) bottom friction parameterizations. Key Points: Evaluation of ADCIRC, FVCOM, SELFE for nor'easter coastal inundation Wave‐current interaction important in forecasting nor'easter coastal inundation. Model performances depend on methods of current‐wave coupling